PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA DI KELAS XI MIPA 1 SMA NEGERI 3 SAMARINDA SEMESTER GENAP TAHUN PELAJARAN 2022/2023 - Darmadianingsih Darmadianingsih (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2023)
The low level of students' understanding of Physics subjects in class XI MIPA 1 SMA Negeri 3 Samarinda has encouraged researchers to improve learning. Learning improvements are carried out through Classroom Action Research (PTK) with 2 cycles and each cycle consists of 3 meetings. The aim of this research is to improve student learning outcomes in Physics subjects by implementing the Discovery Learning model. This research showed that there was an improvement in the learning process. The results of data processing shows that 27 students (75%) had completed their studies with an average score of 75.67 in the pre-cycle, increasing to 32 students (88.89%) had completed their studies with an average score of 80. 22 in cycle I, and 36 students (100%) completed their studies with an average score of 87.78 in cycle II. This means that from pre-cycle to cycle I, students who completed their studies increased by 5 people, and from cycle I to cycle II, students who completed their studies increased by 4 students. Students have completed their studies in the sense of getting a score of 70, this score of 70 is the Criteria of success (KKM). Based on the results above, it can be concluded that: